INCLUSIVE EDUCATION AND GENDER ISSUES IN ISLAMIC INSTITUTIONS - Baisuni Baisuni; Abdul Malik Najamuddin; Zamroni Zamroni (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2025)
Education is a fundamental right guaranteed in Islam for every individual regardless of gender. However, in some Muslim countries, women often face barriers in accessing equal education. This study aims to examine the challenges of gender equality in Islamic education and find solutions that are in accordance with Islamic principles. This study uses a literature study method with a descriptive qualitative approach, utilizing primary sources such as the Quran and Hadith, as well as secondary sources such as journal articles, books, and education policy reports. The research findings reveal that gender barriers in education are caused by inflexible religious interpretations, restrictive social norms, and less inclusive education policies. Nevertheless, several countries such as Indonesia, Turkey, and Tunisia have succeeded in reducing the gender gap through education policies that support women. Islam, as a religion that places justice as a primary principle, has great potential to be a solution to this problem. This study concludes that gender equality in education can be achieved through an inclusive understanding of Islam and the formation of policies that favor women.